Impoliteness Strategy Used By Netizen In The Comment Column On Nadiem Makarim’s Instragram Post About Online Policy - Romauli Siahaan; Christina Natalina Saragi; Usman Sidabutar; Elza Lisnora Saragih (Innovative: Journal Of Social Science Research, 2023)
This study aimed to find out the types of impoliteness strategies based on Jonathan Culpeper theory, and the dominant impoliteness strategies that used by the netizen on Nadiem Makarim’s Instagram post about online policy. This study was conducted by applying descriptive qualitative method. The source of the data was taken from comments column posted by netizens on Nadiem Makarim’s Instagram Account. The technique for analyzing the data is qualitative research. The results of this research showed that there are four impoliteness are used, which are Bald on Record, Positive Impoliteness, Negative Impoliteness, and Sarcasm/Mock Politeness. There were 80 comments. In total there are 4 comments on Bald on Record (5%), 36 comments on Positive Impoliteness (45%), 28 comments on Negative Impoliteness (35%) and 12 comments on Sarcasm/Mock Politeness (15%). Based on the comments that have been analyzed, the researcher concluded that the dominant Impoliteness Strategies that is used by netizens was Positive Impoliteness. The researcher found that the netizens mostly used positive impoliteness to express their negative attitude on giving online comments on Nadiem Makarim’s Instagram Account. The reason could be, that in comparison to other strategies, these have a large number of sub- strategies that support positive and negative impoliteness strategies, such as ignore, uncaring, seek disagreement, scom, ridicule the other, frighten, and so on.